PERSEPSI PEKEBUN KELAPA SAWIT TERHADAP TAUKE DI KELURAHAN SIMPANG KANAN KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR : Persepsi Pekebun Kelapa Sawit Terhadap Tauke - Rokaya, Putri; Yulida, Roza; Novian, Novian (JALOW | Journal of Agribusiness and Local Wisdom, 2023)
This research aims to find out 1) the characteristics of tofu and oil palm growers, 2) the perception of oil palm growers towards the available tofu and 3) the level of importance and the level of trust of oil palm growers. The method used is the survey method. The sample in this research is 30 oil palm farmers and 3 tofu people. The analysis technique used is qualitative descriptive, which is measured by likert scale and cartesian diagram. The result is that all oil palm farmers are of productive age, educated at the basic level, belong to medium families, the production of fresh fruit marks/month is less, regional minimum wage income, production is classified as medium, enough experienced, land area is relatively large. All people are of productive age, have secondary education, have experience, earn above the regional minimum wage, have a high level of production, and have a large number of dependents. Farmers trust touke as a helper for farmers in terms of marketing their agricultural products, with the highest level of trust especially the touke's willingness to give loans and owe saprodi, the lowest being a relationship of intimacy. The level of importance and the level of trust of oil palm growers in the main priority is the price, the attribute that must be maintained is to provide loans. Attributes that are low priority are keeping promises, close relationships, suggestions from friends and family relationships. Then the excessive indicator is the attribute of familiarity and advice from friends.